Binding of Heparin Fractions to von Willebrand Factor: Effect of Molecular Weight and Affinity for Antithrombin III - Baruch, D; Ajzenberg, Nadine; Denis, Cécile; Legendre, Paulette; Lormeau, Jean-Claude; Meyer, Dominique (Thrombosis and Haemostasis, 1994)
To investigate the influence of the structure of heparin on its binding to vWF, we compared heparin fractions of different molecular weight (MW) or affinity for antithrombin III (ATIII). We studied the interaction of purified 125I-vWF or plasma vWF, labeled with a pool of 125I-monoclonal antibodies to vWF, with unfractionated heparin immobilized on agarose beads. Fractions were compared as competitors of these interactions and their effect was quantitated by their half-maximal inhibition (IC50). When the MW of the fractions decreased, especially below 7500, their IC50 increased, indicating that the affinity of the fractions for vWF decreased with their MW. Using heparin-derived oligosaccharides, we also demonstrated that a minimal chain length of 18 monosaccharides was required for heparin binding to vWF. In addition, different fractions with low affinity for ATIII were compared as competitors of 125-vWF binding to heparin-agarose. Despite a very low content of ATIII binding sites, some fractions retained a low IC50. Thus, heparin interaction with vWF is independent of the presence of the ATIII binding site and is mostly dependent on the length of the heparin chain. These data suggest that unfractionated heparin is a more potent inhibitor of vWF-dependent functions than low MW heparin fractions.